Self-efficacy Matematika dan Mengajar Matematika Mahasiswa Calon Guru Matematika - Meika, Ika; Mauladaniyati, Ratu; Sujana, Asep; Berliana, Risma (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
In-depth mathematics self-efficacy research is particularly important in educational contexts. Because understanding students' levels of self-efficacy can help identify factors that influence student academic performance and develop more effective learning strategies. For this reason, this research aims to describe mathematics self-efficacy and mathematics teaching self-efficacy among prospective mathematics teacher students. The research method was descriptive qualitative with an instrument in the form of a self-efficacy questionnaire and the research subjects were 13 second semester students of the mathematics education study program at Mathla'ul Anwar University. The results show that student teachers' mathematics self-efficacy and mathematics teaching are at a moderate level. These two self-efficacy are not much different, although the average value of mathematics teaching self-efficacy is lower than mathematics self-efficacy.